(untitled) (Bangladesh Journal of Medical Science, 2023)
Dental implants have become the preferred treatment option for missing teeth replacement due to their functional and restorative benefits. However, placing implants in the esthetic zone remains a challenge due to anatomical factors and the need for optimal emergence profile. The use of custom abutments and regenerative techniques in this case report resulted in a successful implant-supported restoration with excellent functional and aesthetic outcomes. The case highlights the importance of proper treatment planning and the use of advanced techniques in implant dentistry to achieve optimal results. Bangladesh Journal of Medical Science Vol.22 (Special Issue) 2023 p.100-105